Blood Metagenome in Health and Psoriasis - Korotky, Nikolay; Peslyak, Mikhail (Frontiers in Medicine, 2020)
Survey and analytical assessment of the results of fundamental works on studying blood metagenome is carried out. All works on determining bacterial DNA concentration in whole blood of healthy people are reviewed. Detailed comparison of characteristics of 16S-test and WMS-test is carried out and published in Supplement S1. One of main goals of this review is to identify the drawbacks and mistakes which the studied works contain, particularly to emphasize the crucial importance of determining total concentration of bacterial DNA for comparing patients’ metagenomes with those of healthy people as well as for comparing patients’ metagenomes with each other. Controlling the level and composition of contamination is equally important. The absence of high-quality contamination control at each step (or at certain steps) of the research significantly reduces the reliability of achieved results. The given review is the first attempt to analyze and systematize the results of blood metagenome studies, whose number has increased considerably in the last few years. The review has been carried out as part of preparation for implementing a project on complex studying metagenomes of whole blood and skin biopsies at psoriatic patients.